Analisis Pengaruh PAD, DAU, DAK dan DBH terhadap indeks pembangunan manusia seluruh provinsi di Kalimantan tahun anggaran 2015-2019 - Evi Sulastri; Efendri Efendri (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This study aims to determine the effect of Regional Original Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH) on the Human Development Index (IPM). The population in this study were districts/cities in all provinces in Kalimantan for the 2015-2019 fiscal year. This study uses the purposive sampling method in determining the research sample to produce as many as 200 research samples. The data used in this study is secondary data originating from the Regional Revenue and Expenditure Budget (APBD) and the Central Statistics Agency (BPS). The hypothesis testing in this study is multiple linear regression and descriptive statistical tests using SPSS 26. The results of this study indicate that: 1) Regional Original Revenue (PAD) has a positive and significant effect on the Human Development Index (IPM), 2) General Allocation Funds (DAU) have a negative and significant effect on the Human Development Index (IPM), 3) The Special Allocation Fund (DAK) has a negative and significant effect on the Human Development Index (IPM), 4) Revenue Sharing Funds (DBH) have no effect on the Human Development Index (IPM). 5) PAD, DAU, DAK, and DBH simultaneously affect the IPM.